Workshops on gender equality in the rural sector through the use of communication as a method - Alfonso García, Marcial; Mendoza Domínguez, Imandra; Martínez Rivera, Taimy (Scripta Mundi, 2023)
This work identifies the ways of life of women and men in the rural sector of the cuban municipality of Aguada de Pasajeros and the unequal opportunities for both. Based on the above, the objective is determined: to propose a system of workshops through the use of communication to guarantee gender equity in rural aguadense. The elaboration of the workshops was preceded by the diagnosis and characterization of the particularities of rural women, of the potentialities of the Municipal University Center for the realization of training actions, as well as of the perceptions about gender equality and communication. For its execution, the human and material resources present in the municipality were taken into account, in order to comply with the intended purpose. The application of the workshop proposal allowed rural women to acquire knowledge about the subject and offered new opportunities for the enjoyment of the full exercise of rights, a greater contribution of women in socio-labor life, as well as justice and equity between women and men in the rural sector of aguadense.